Review: Novel treatment strategies targeting alpha‐synuclein in multiple system atrophy as a model of synucleinopathy. (February 2016) - Valera, E.; Monzio Compagnoni, G.; Masliah, E.
Abstract : Neurodegenerative disorders with alpha‐synuclein (α‐syn) accumulation (synucleinopathies) include Parkinson's disease (PD), PD dementia, dementia with Lewy bodies and multiple system atrophy (MSA). Due to the involvement of toxic α‐syn aggregates in the molecular origin of these disorders, developing effective therapies targeting α‐syn is a priority as a disease‐modifying alternative to current symptomatic treatments. Importantly, the clinical and pathological attributes of MSA make this disorder an excellent candidate as a synucleinopathy model for accelerated drug development. Recent therapeutic strategies targeting α‐syn in in vivo and in vitro models of MSA, as well as in clinical trials, have been focused on the pathological mechanisms of α‐syn synthesis, aggregation, clearance, and/or cell‐to‐cell propagation of its neurotoxic conformers. Here we summarize the most relevant approaches in this direction, with emphasis on their potential as general synucleinopathy modifiers, and enumerate research areas for potential improvement in MSA drug discovery.